A comprehensive study of particulate and gaseous emissions characterization from an ocean-going cargo vessel under different operating conditions. (15th February 2020) - Zhao, Jingbo; Zhang, Yanjie; Yang, Zhiwen; Liu, Yan; Peng, Shitao; Hong, Ningning; Hu, Jianbo; Wang, Ting; Mao, Hongjun
Abstract: This study investigated particulate and gaseous emission factors (EFs) from an ocean-going cargo vessel operating under different real-world conditions. EFs were determined for criteria gaseous (including NO, NO2, CO, CO2, SO2 ) and particulate pollutants (including PM2.5 and PM2.5 components, such as organic carbon, elemental carbon, BC, water-soluble inorganic ions and metal elements). The results showed that the gaseous emissions were dominated by CO2 and NO, the EFs of which were ranging from 489 g/kWh to 1040 g/kWh, and 11.2 g/kWh to 29.1 g/kWh, respectively. And the EFs of PM2.5 were ranging from 0.13 g/kWh to 1.12 g/kWh. Vanadium, silicon, calcium and nickel were the main contributors to the presence of inorganic metal elements. Marine diesel oil (MDO) and heavy fuel oil (HFO) were used in the cargo vessels sailing along the coastline and in the ocean, respectively. When using MDO instead of HFO, the SO2, NOX and PM2.5 emissions were reduced by 5%, 90% and 60%, respectively. There seemed no obvious effect of the fuel type on the CO2 emission. Besides, the CO2 and SO2 emissions of HFO were linearly correlated with PM2.5 . Moreover, the energy efficiency management system (EEMS) was used to estimate the relationship between emissions and engine working conditions. Effective thermal efficiency ( η et ) was calculated based on combustion status. CO and BC decreased with increasing η et for both HFO and MDO, while NO increased with increasing η et . These results could provide important data support for the use of certification values for emissions inventories. Highlights: Comprehensive characterization of emissions at different engine settings. The engine conditions were measured by energy efficiency management system (EEMS). Effective thermal efficiency ( η et ) was calculated based on combustion status. Correlations of gaseous emissions with particulate emissions was estimated.